2012
DOI: 10.1096/fj.12-222257
|View full text |Cite
|
Sign up to set email alerts
|

Secreted protein lipocalin‐2 promotes microglial M1 polarization

Abstract: Activated macrophages are classified into two different forms: classically activated (M1) or alternatively activated (M2) macrophages. The presence of M1/M2 phenotypic polarization has also been suggested for microglia. Here, we report that the secreted protein lipocalin 2 (LCN2) amplifies M1 polarization of activated microglia. LCN2 protein (EC 1 μg/ml), but not glutathione S-transferase used as a control, increased the M1-related gene expression in cultured mouse microglial cells after 8-24 h. LCN2 was secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
139
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 171 publications
(150 citation statements)
references
References 67 publications
10
139
1
Order By: Relevance
“…27 Interestingly, also microglial cells were shown to respond to LCN2, which seems to favor their polarization into a M1-activated phenotype. 28 Here, we show that LCN2 is not produced by microglia in response to Ab , both in astrocyte-enriched cultures (o5% microglia) and in microglia-enriched cultures.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…27 Interestingly, also microglial cells were shown to respond to LCN2, which seems to favor their polarization into a M1-activated phenotype. 28 Here, we show that LCN2 is not produced by microglia in response to Ab , both in astrocyte-enriched cultures (o5% microglia) and in microglia-enriched cultures.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have shown that different cell populations from the CNS are able to upregulate the expression of Cxcl10 after treatment with LCN2, which, in turn, promotes the activation and migration of glial cells within the CNS. 16,28 Moreover, Ab led to an overexpression of Hmox1 and Fth in CP epithelial cells and in astrocytes. It is well established that both CP epithelial cells and astrocytes have an important role in brain iron metabolism and changes in the expression of ironrelated genes are often correlated with alterations in the level of intracellular/extracellular iron ratio under stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice lacking LCN2 have a markedly reduced M1-related gene expression in microglia after lipopolysaccharide injection. 26 Expression of LCN2 was sensitive to cytotoxic agents, and inflammatory activation of microglia can lead to LCN2 upregulation. Meanwhile, LCN2 expression in BV-2 microglia induces cell morphologic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Although LCN2 is considered as being mainly expressed in astrocytes, 12,14,23,24 where its secretion may be neurotoxic, 24 other cell types may express LCN2. Thus, inflammatory cells, such as microglia and neutrophils 15,25,26 can also express LCN2. The effects of LCN2 on microglia are complex.…”
Section: Discussionmentioning
confidence: 99%